Necrostatin-1 alleviates temporomandibular joint osteoarthritis and inhibits chondrocyte senescence and necroptosis possibly via p53/ MAPK downregulation - Zhang, Ying; Cai, Wenyi; Wu, Antong; Li, Rui; Li, Xin; Zheng, Kaihan; Lin, Yufu; Zhang, Qingbin; Cao, Wei (Frontiers in Bioengineering and Biotechnology, 2025)
Temporomandibular joint osteoarthritis (TMJ-OA) is a prevalent oral and maxillofacial disorder characterized by a complex etiology and pathogenesis. Targeting and eliminating senescent chondrocytes is emerging as a promising therapeutic strategy for TMJ-OA. Necrostatin-1 (NEC1), a receptor-interacting protein kinase 1 (RIPK1)-targeted necroptosis inhibitor, has shown potential therapeutic effects in various skeletal disorders. However, the therapeutic implications of NEC1 in TMJ-OA, particularly regarding its effect on chondrocyte senescence, remain unclear. In this study, models of TMJ-OA were established by utilizing monosodium iodoacetate (MIA) to induce TMJ-OA in rats. NEC1 was administered via intra-articular injection. Treatment with NEC1 significantly alleviated the progression of TMJ-OA in rats, reduced pain, and restored cartilage integrity. In vitro, NEC1 (40 μM) exhibited cytoprotective effects on Rat primary condylar chondrocytes (rPCCs), preserving cell viability and reducing cellular senescence markers (Cdkn1a and Cdkn2a) following IL-1β+TNF-α treatment. Additionally, NEC1 inhibited the expression of extracellular matrix (ECM) degradation markers (MMP3, MMP9, MMP13) and programmed necrosis indicators (p-MLKL) in chondrocytes. NEC1 downregulated inflammation-induced p53 and MAPK signaling pathways in rPCCs.Thus, NEC1 demonstrated a significant capacity to slow the progression of TMJ-OA by inhibiting and alleviating condylar chondrocyte senescence, necrosis, and ECM degradation, suggesting its potential role in the treatment of TMJ-OA.